Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I.; Tomás-Barberán, Francisco a (Journal of Agricultural and Food Chemistry, 2007)
Ellagitannin-containing foods (strawberries, walnuts, pomegranate, raspberries, oak-aged wine, etc.) have attracted attention due to their cancer chemopreventive, cardioprotective, and antioxidant effects. Ellagitannins (ETs) are not absorbed as such but are metabolized by the intestinal flora to yield urolithins (hydroxydibenzopyran-6-one derivatives). In this study, Iberian pig is used as a model to clarify human ET metabolism. Pigs were fed either cereal fodder or acorns, a rich source of ETs. Plasma, urine, bile, lumen and intestinal tissues (jejunum and colon), feces, liver, kidney, heart, brain, lung, muscle, and subcutaneous fat tissue were analyzed. The results demonstrate that acorn ETs release ellagic acid (EA) in the jejunum, then the intestinal flora metabolizes EA sequentially to yield tetrahydroxy- (urolithin D), trihydroxy- (urolithin C), dihydroxy- (urolithin A), and monohydroxy- (urolithin B) dibenzopyran-6-one metabolites, which were absorbed preferentially when their lipophilicity increased. Thirty-one ET-derived metabolites were detected, including 25 urolithin and 6 EA derivatives. Twenty-six extensively conjugated metabolites were detected in bile, glucuronides and methyl glucuronides of EA and particularly urolithin A, C, and D derivatives, confirming a very active enterohepatic circulation. Urolithins A and B as well as dimethyl-EA-glucuronide were detected in peripheral plasma. The presence of EA metabolites in bile and in urine and its absence in intestinal tissues suggested its absorption in the stomach. Urolithin A was the only metabolite detected in feces and together with its glucuronide was the most abundant metabolite in urine. No metabolites accumulated in any organ analyzed. The whole metabolism of ETs is shown for the first time, confirming previous studies in humans and explaining the long persistency of urolithin metabolites in the body mediated by an active enterohepatic circulation.
From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 17990850
Keywords: Animal; Animals; bile; bioavailability; Biological Availability; Body Fluids; Body Fluids: chemistry; Cereals; Cereals: chemistry; colon; diet; ellagic acid; Ellagitannin; gall bladder; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: metabolism; Hydrolyzable Tannins: pharmacokinetics; intestine; metabolism; Models; Quercus; Seeds; Seeds: chemistry; Swine; Swine: metabolism; Tissue Distribution; urolithin

Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans (Journal of Agricultural and Food Chemistry, 2007)
Ellagitannin-containing foods (strawberries, walnuts, pomegranate, raspberries, oak-aged wine, etc.) have attracted attention due to their cancer chemopreventive, cardioprotective, and antioxidant effects. Ellagitannins (ETs) are not absorbed as such but are metabolized by the intestinal flora to yield urolithins (hydroxydibenzopyran-6-one derivatives). In this study, Iberian pig is used as a model to clarify human ET metabolism. Pigs were fed either cereal fodder or acorns, a rich source of ETs. Plasma, urine, bile, lumen and intestinal tissues (jejunum and colon), feces, liver, kidney, heart, brain, lung, muscle, and subcutaneous fat tissue were analyzed. The results demonstrate that acorn ETs release ellagic acid (EA) in the jejunum, then the intestinal flora metabolizes EA sequentially to yield tetrahydroxy- (urolithin D), trihydroxy- (urolithin C), dihydroxy- (urolithin A), and monohydroxy- (urolithin B) dibenzopyran-6-one metabolites, which were absorbed preferentially when their lipophilicity increased. Thirty-one ET-derived metabolites were detected, including 25 urolithin and 6 EA derivatives. Twenty-six extensively conjugated metabolites were detected in bile, glucuronides and methyl glucuronides of EA and particularly urolithin A, C, and D derivatives, confirming a very active enterohepatic circulation. Urolithins A and B as well as dimethyl-EA-glucuronide were detected in peripheral plasma. The presence of EA metabolites in bile and in urine and its absence in intestinal tissues suggested its absorption in the stomach. Urolithin A was the only metabolite detected in feces and together with its glucuronide was the most abundant metabolite in urine. No metabolites accumulated in any organ analyzed. The whole metabolism of ETs is shown for the first time, confirming previous studies in humans and explaining the long persistency of urolithin metabolites in the body mediated by an active enterohepatic circulation.
From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)